Strategi Diferensiasi sebagai Upaya Mewujudkan Keunggulan Bersaing pada UKM Furniture - Zahara, Arsy Permatasari; Danial, R. Deni Muhammad; Samsudin, Acep (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
Competitive advantage is an ability to create products that have more added value that can be used as strength to win the competition. The study was conducted on the furniture business of the City of Sukabumi, which wants to win the competition in an increasingly increasing number of competitors with similar businesses. The purpose of this study is to determine and understand the effect of differentiation strategies as an effort to realize competitive advantage in furniture SMEs. Starting with the desire to realize competitive advantage, the company needs to create a difference or privilege that is not owned by competitors to be used as strength in winning the competition. The method used to process this research data is quantitative with associative methods. With 50 respondents, namely furniture business owners or managers using IBM SPSS Version 23. The results of this research show that this research is categorized as having a very strong correlation with a value of 0.896. So that the conclusions in this research reveal the differentiation strategy has an influence in realizing competitive advantage by creating a difference both from product, service, personnel and image.